Spirituality in African-American Breast Cancer Patients: Implications for Clinical and Psychosocial Care - Sheppard, Vanessa B. (Journal of religion and health, 2018)
Spirituality has been shown to be important to many individuals dealing with a cancer diagnosis. While African-American breast cancer survivors have been reported to have higher levels of spirituality compared to White women, little is known about how levels of spirituality may vary among African-American breast cancer survivors. The aims of this study were to examine factors associated with spirituality among African-American survivors and test whether spirituality levels were associated with women's attitudes about treatment or health care. The primary outcome, spirituality, was nine-item scale (Cronbach's a = .99). Participants completed standardized telephone interviews that captured sociocultural, healthcare process, and treatment attitudes. Medical records were abstracted post-adjuvant therapy for treatment and clinical information. In bivariate analysis, age was not correlated with spirituality (p = .40). Married/living as married women had higher levels of spirituality (m = 32.1) than single women (m = 30.1). Contextual factors that were associated with higher levels spirituality were: collectivism (r = .44; p < 0.0001, Afrocentric worldview (r = .185; p = .01), and self-efficacy scale (r = .17; p = .02). In multivariable analysis, sociodemographic factors were not significant. Collectivism remained a robust predictor (p < 0.0001). Attitudes about the efficacy of cancer treatment were not associated with spirituality. The high levels of spirituality in African-American survivors suggest consideration of integrating spiritual care within the delivery of cancer treatment. Future studies should consider how spirituality may contribute to positive coping and/or behaviors in African-American women with high levels of spirituality.